IMPLEMENTATION OF EYES TEACHER LEARNING STRATEGIES IPS LESSONS AT SMP NEGERI 27 MAKASSAR - Syamsuriyanti (SOLIDARITY: Journal of Social Studies, 2022)
This research aims to find out the picture of the learning strategy of teachers of IPS subjects at SMP Negeri 27 Makassar. This study used quantitative research with a population of all 1st and 2nd-grade students at SMP Negeri 27 Makassar, while the sample was 68 students. Data collection is carried out using observation data collection techniques, interviews, questionnaires, and documentation. This data is analyzed using descriptive statistical analysis, simple linear regression analysis, and product moment analysis. The results showed that the picture of the learning strategy of ips subject teachers at SMP Negeri 27 Makassar belonged to the category of